Igniting Change in Business: Leading & Managing Transformational Change - Amir Azhar (ZBW - Leibniz Information Centre for Economics, 2021)
Organizational growth and survival depend on how they adapt to changing business environment, which requires continually evaluating their business model. Therefore, to compete in a rapidly changing business environment organizational change is absolutely necessary. Organizations have been defined as technical (i.e. organizational structure, framework and reporting channel, etc.) and - socio (culture, values, and beliefs) systems. Leading and managing change require leaders to master both aspects of organization systems. This paper explores how leaders and managers are engaged in organizational change. The study highlights barriers to change and suggested what practical measures can be carried out to bring about change. The research combined theoretical views and real-world examples, with a strong conclusion that shows how bringing change into organizations, is critical to the business world to survive and grow.
Keywords: 330; Change Management; Transformational Change; Leading Change; Barriers to Change